Validity of the British system for anticoagulant control using the national reagent - Alderson, M. R. (1970)
The national system for anticoagulant control depends on drawing the best line obtained by visual comparison of the points representing corresponding prothrombin ratios with the British comparative thromboplastin in the local reagent. This line is then used to correct subsequent values using the local laboratory method of corresponding values in terms of the British comparative thromboplastin. A study has been made of the statistical validity of the recommended system for anticoagulant control using the Quick one-stage test by comparing the line drawn by inspection with the confidence limits of the regression line. There was little difference between the best straight line by visual comparison and the calculated line for the majority of hospitals. The recommended procedure, therefore, provides an adequate conversion of the local method to the British comparative thromboplastin without the need for calculation. The significance of aberrant points is discussed and it is suggested that when more than two of the 12 results fall in this category the standardization procedure should be repeated.